Method for adapting radioacoustic sounding systems of the atmosphere - Kartashov, A.V.; Kondrashov, I.E. (Radiotekhnika, 2024)
Stations of radioacoustic sounding (RAS) of the atmosphere are a promising means of obtaining information about the altitudinal distribution of meteorological parameters in the Earth's atmosphere used in the process of solving current scientific and applied tasks to ensure aircraft flights, weather forecasting, etc. However, the effectiveness of the existing radio-acoustic means is insufficient, and there are practical needs for the development of appropriate prospective structures and algorithms, which will be implemented during the construction of specific stations designed to solve actual applied tasks. The article presents the synthesis of the RAS systems algorithm adaptation performed by changing the frequency of the sounding radio signal to fulfill the Bragg condition when the emitted acoustic pulse signal moves along the sounding path from the standpoint of optimal control theory. Since in the problem of synthesizing the algorithm for controlling the frequency of a radio signal, the disturbing and leading to violations of the Bragg condition during the propagation of an acoustic packet along the sounding path, as well as the process causing measurement errors, are considered as random, this problem is considered as a problem of stochastic optimal control. It is shown that in accordance with the separation theorem, known from the theory of optimal stochastic control, the method of controlling the frequency of a sounding radio signal should include sequentially peformed operations of forming estimates of the information parameter of the scattered radio signal, optimal linear filtering of the obtained estimates, and deterministic control of the frequency of the sounding radio signal.